(untitled) (Persona y Derecho, 2019)
The paper aims to support a view of human rights as essentially characterized by a basic content and in this sense focuses on the notion of basic rights. The key features associated with the notion of human rights – moral embedding and universality – should lead to regard human rights as essentially basic rights. The analysis will (i) argue for a notion of ‘basicness’ that is different from the notion occurring both within the so-called minimalist theories and the one worked out by Henry Shue; (ii) address the link between the idea of basic rights and the doctrine of the minimum core/content and (iii) criticize a deviation from the desirable path, which lies in shifting from the notion of minimum core of rights to the notion of core rights.